Dampak Perubahan Iklim terhadap Kesehatan Masyarakat : Systematic Literature Review - Joko Susanto; Irgi Biantara; Franky Sumarlie; Nur Afnita; Sulur Joyo Sukendro; Cipta Pramana (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Climate change has become one of the greatest challenges facing the world today. The impacts of climate change on human health can be felt through increasing extreme temperatures, the spread of infectious diseases, and increased air pollution. The aim of this research is to determine the impact of climate change on public health. A literature search was conducted through several electronic databases, including Google Scholar and PubMed, to capture articles published from 2020 to June 2025. The article selection process involved several stages of identification and screening based on title and abstract, followed by an assessment of the eligibility of full-text articles based on inclusion and exclusion criteria. All selection stages were documented using a PRISMA flowchart.The results of this study revealed direct and indirect health impacts. It can be concluded that climate change on public health can be influenced by disruptions to physical, biological, and ecological systems, including disruptions originating domestically and internationally. The health impacts of these disruptions include increased respiratory and cardiovascular diseases, injuries and premature deaths related to extreme weather events, changes in the prevalence and geographic distribution of food- and waterborne diseases and other infectious diseases, and threats to mental health.